2020
DOI: 10.1186/s13007-020-00634-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction of yield and root development in wheat under changing water availability

Abstract: Background: Deeper roots help plants take up available resources in deep soil ensuring better growth and higher yields under conditions of drought. A large-scale semi-field root phenotyping facility was developed to allow a water availability gradient and detect potential interaction of genotype by water availability gradient. Genotyped winter wheat lines were grown as rows in four beds of this facility, where indirect genetic effects from neighbors could be important to trait variation. The objective was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…S3). Moreover, the large environmental variance (low r number) in root relationships may have been caused by spatial effects reported in previous studies ( Guo et al, 2020;Zhou et al, 2021). Compared to traditional 2D…”
Section: D and 3d Imaging For Studying Root-soil Relationshipsmentioning
confidence: 78%
“…S3). Moreover, the large environmental variance (low r number) in root relationships may have been caused by spatial effects reported in previous studies ( Guo et al, 2020;Zhou et al, 2021). Compared to traditional 2D…”
Section: D and 3d Imaging For Studying Root-soil Relationshipsmentioning
confidence: 78%
“…This might be because both managements were tested under nitrogen-limited conditions or the experiment only covered the early developmental stages. For example, Guo et al (2020) reported that low nutrients in optimal irrigated growth conditions might contribute to the absence of genotype-by-water availability interaction in wheat. On the other hand, the significant management effect suggests that PGPB can promote plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…The deep rooting characteristics of wheat are important traits that impact nutrient and water acquisition from the subsoil ( Atkinson et al , 2019 ; Bai et al , 2019 ; Guo et al , 2020 ). However, Guo et al (2020) report that low heritability in deep rooting was caused by very large environmental variance due to spatial effects and measurement errors. It is therefore important to understand how environmental factors contribute to variability in root depth.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large environmental impact of soil on rooting depth, deterorating soil conditions arising from contemporary agriculture might well explain poor rooting, as suggested by White et al (2015) . It is of concern that Guo et al (2020) observed that in a selction of 84 wheats from high-yielding northern and central European varieties and advanced breeding lines, the heritability of deep rooting was low. This was partly attributed to high environmental variability including heterogeneity in soil type which can often be considerable.…”
Section: Discussionmentioning
confidence: 99%